The Examination Of The Schools In Denizli According To University Entrance Exam By Multivariate Statistical Methods - Gülel, Ferda Esin; Çağlar, Atalay (European Scientific Journal, ESJ, 2016)
The aim of the university entrance exam is two folds. First, it identifies the students that deserve the education after high school graduation. Second, the grades taken from this exam specify the quality of the high schools. These grades are important for the schools which are in competition with the others. In the present study, the schools in Denizli are examined according to the grades of the students who are graduates or senior class students. Multivariate statistical methods are used in the data analysis. The data of the study were gathered from 2012 Student Selection and Placement Exam statistics. The findings and the implications of the study is discussed accordingly.